(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: To evaluate the incidence of gallbladder content spillage and the factors contributing to it during laparoscopic cholecystectomy.Materials and methods: The research comprises 100 consecutive laparoscopic cholecystectomy patients. The data was collected prospectively in accordance with the proforma, which documented the patient's detailed diagnosis, preoperative physical and ultrasound abdomen findings, intra-operative details such as technique, spillage of stones, cause of spillage, method and port of specimen extraction, duration of surgery, and postoperative events and complications. A one-week, one-month, six-month, and one-year postoperative follow-up was undertaken.Results: In our research, 100 consecutive laparoscopic cholecystectomy procedures were performed. There were 63 female patients and 37 male patients among them. The research group's average age was 49.85±11.58 years. The majority of the patients had several 1 cm movable gallstones. In 88% of patients, the procedure lasted between 30 and 60 minutes. Adhesions of varied degrees were found in 78% of the cases, resulting in a 7% conversion rate. Minimal bleeding was seen in 51% of the instances, significant haemorrhage in 37% of the cases, and no bleeding was observed in 12% of the cases. Gallstone leakage happened in 20% of the instances. In our research, the complication rate for laparoscopic cholecystectomy was 3%; however, the complication rate from spilled gallstones was 1%. At 1, 6, and 12 months of post-operative follow-up, no complaints about the procedure were noted.Conclusion: Leakage of gallstones and bile after routine laparoscopic cholecystectomy is uncommon and usually results in very minor problems. To prevent difficulties after a spill, it is crucial to remove the stones and do a peritoneal toileting.